Nonprofit financial growth and path dependency - Georg von Schnurbein (University of Basel, Center for Philanthropy Studies (CEPS), 2017)
Financing non-profit organizations (NPOs) differs from financing business companies. Based on a literature review this article highlights that many aspects of nonprofit development are defined at the stage of the organizations' foundation. Thus, we apply the path dependence theory as a basis for an analysis of nonprofit finance and the questions, if a static organizational behavior influences nonprofit finance, and which factors influence financial growth in nonprofits. The results highlight that organizations in a lock in status built less organizational capital and have lower revenues. For practical application, nonprofits face the challenge to develop a stable - i.e. projectable - mix of financial resources. This means to build up a holistic financial management that matches donations, government spending, own revenues, and financial revenues under consideration of the NPO's purpose and eliminating the threat of becoming inflexible.
Keywords: 330